Dissatisfaction toward O2O websites: expectation disconfirmation and justice perspective. Issue 1 (26th March 2021) - Che, Tong; Ji, Meng; Zheng, Xiabing; Feng, Bo
Abstract : Purpose: The online-to-offline (O2O) business is developing rapidly and is highly popular in many countries. Nevertheless, O2O suffers from a large number of customer complaints that result in consumer loss. Focusing on the O2O context, this study integrates expectation disconfirmation theory (EDT) and justice theory to investigate consumers' dissatisfaction toward O2O websites. Design/methodology/approach: A research model was proposed and tested using 329 survey responses. Findings: Results show that the identified website disconfirmation and offline service disconfirmation could lead to consumer dissatisfaction. Importantly, the impacts of disconfirmation factors are contingent upon the justice perception of consumers. When a transaction is perceived as unfair, website disconfirmation arouses a higher level of dissatisfaction, and the negative emotions could transfer from O2O and damage the website's reputation. Originality/value: This study explores the continuance intentions of customers toward O2O websites from a dissatisfaction perspective, with insights for future service studies and O2O service managers.